Förekomst av kontaminanter i importerad fisk - Arzoomant, Attal (2014)
A literature review of contaminants; cadmium, methylmercury, dioxins, and PCB, for eleven different fish species (Greenland halibut, gilt headed bream, sea bass, wolffish, hoki, ocean perch, angler, Nile perch, pangasius, red snapper and tilapia) that were selected in concurrence with the National Food Administration. The result can be used by the National Food Administration to gain further knowledge about the different fish species to be able to continue to give advice to varied risk category and the public. The gilt headed bream and sea bass were the only fishes whose values for mercury exceeded the limit of 0,5 mg/kg (EU Reg. 1881/2006). In the angler, Nile perch and pangasius the mean value of mercury didn’t exceed the limit, however in some individuals the mercury content did exceed what is allowed. Regarding Greenland halibut and red snapper insufficient data was found to draw any conclusions. For the ocean perch no data was found.